Sei sulla pagina 1di 8

# LOGARITHMS FOR BIOLOGISTS

Eqn. 1

Let b1 = b2 = b3 = ……………….. = b r = ( b)
And b1 x b2 x b3 x b4 x .. ……………….x b r = br = p
In the Eqn. br = p , r is the index or power of b that corresponds to the
value p
Then
r is the Logarithm to the base b of p which is written as
r = log b p ; here p is Antilog i.e antilog b r = p
Note antilog b r = b r
i.e.
Logarithm to the base b form the inverse to exonentiaals to the base b
If bs = q then , s = log b q
If b = 16 and q = 4 then s = ½ since 16 1/2 = 4
i.e. 1/ 2 = log 16 4 and antilog 16 1/2 = 4 (since, antilog 16 1/2 = 16 1/2 )

Eqn. 2

If p x q = m then , m = br x bs = b (r + s)
Now b ( r + s) = m ; therefore , ( r + s ) = log b m
But r = log b p and s = log b q

Therefore ,

## log b p + log b q = log b ( pq )

therefore,
Logarithm of the product of two numbers is equal to the
summation their
individual logarithm

## log b m = log b p * q = log b p + log b q

.
Law of subtraction of logarithm:

## Note : log b 1 - log b q = log b ( 1 / q )

but , log b 1 = 0
therefore, - log b q = log b ( 1 / q )

Example : 1
Evaluate the logarithm to the base 3 of Z = XY when X = 9 and Y = 27.
X=9=32 and Y = 27 = 3 3
Therefore , log 3 9 = 2 and log 3 27 = 3

Now , Z = X Y = 9 X 27 = 243

## Using Eqn. 1 and 2,

log 3 Z = log 3 243 = log 3 X + log 3 Y = log 3 9 + log 3 27
= 2+3 = 5
( 243 = 3 5 Therefore , log 3 243 = 5 )

## Note: Logarithm only exist for posiive numbers :

log y x
Supposing 10 = x , then y must have a value such that y = 10

Eqn. 3

## log b b = 1 ( Let bm = b i.e. m = 1 ; therefore log b b = m = 1 )

log 9 9 = 1
243 = 3 5 # 27 = 9 x 3 = 9 1 x 9 1/2 = 9 ( 1+1/2 )
= 9 3/2 #

Eqn. 4

## law for logarithms of power terms :

Let U = b p and V = U q
Then , V = ( b p ) q = b p q
i.e. log b V = pq
Now, log b U = p therefore , log b V = p q = q log b U
Again , V = U q
therefore ,
log b V = log b ( U q ) = q . log b U

## Note : log a ( nx ) = I / n log a x ,

since nx = x 1 / n
and ,therefore,
log a ( nx ) = log a x1/ n = 1/ n log a x

Example : 2
Evaluate log 3 243;
243 = 3 5 , so log 3 243 = log 3 (3 5 ) = 5 log 3 3
using Eqn. 3 ( log 3 3 = 1), log 3 243 = 5 x 1 = 5

Eqn. 5

## Usual and convenient base for logarithm is b = 10

Referring to Example 1,
let m = log 3 9 and n = log 3 27
it can be shown that m + n = 2.3856* i.e. 10 2.3856 = 243
*( m=0.9542 , n = 1.4314 )
it has been shown that
243 = 3 5 = 9 5/2 = 10 2..3856
therefore,
log 3 243 = 5 log 9 243 = 5 / 2 log 10 243 = 2.3856
The bases of these logarithms are respectively 3 , 9 and 10
Equation for conversion of one base b to another base c is :

## Let m = log b x then, b m = x . Let c n = x .

therefore , n = log c x
therefore, log c x = log c ( b m ) = m log c b
It follows from m = log b x ,
log c x = ( log b x ) * (log c b ) or log b x = log c x / log c b

## If c = x , then log c x = log x x = 1 and log b a * log a b = 1

Example : 3
Given log 2 64 = 6 ; Evaluate log 4 64
log 2 64 = 6 i.e 2 6 = 64
2 = 4 1/2 i.e. log 4 2 = 1/2
using Eqn. 4
log 4 64 = log 2 64 * log 4 2
= 6 * 1/2
= 3

## Consider a problem of cell division as an event in Biology

a mother cell divides into two
which in turn divides into
4=22
In such events logarithm to the base 2 are often useful in biology
Considering a particular stage of 4096 cells
How many generation it takes to get 4096 cells ?
log 2 4096 = log 2 ( 2 ) 12 = 12 * log 2 2 = 12 * 1 = 12
12 is the power to which 2 must be raised to get 4096
or , to get 4096 cells 12 generations are required.

## The following practicable systems are in use :

g x the common logarithm of x to base 10
ln x the natural logarithm of x to base e (= 2.718 appxly. )
or Napierian logarithm
lb x the binary logarithm of x to base 2

Calculator has key ‘log’ which gives the log of any number with base 10 . e.g.
to calculate log 10 26

## press 2 6 log = 1.415

Problems :
1) log 10 4.02 = 0.6042 ; evaluate log 10 4020 and log 10 0.402
2) Evaluate the number of generaton required to get 1024 cells by successive cell
division
3) Find x when , (a) log 10 x = 3 (b) log 7 x = 1 (c) log 1/3 x = - 4
4) Find antilog , (a) antilog 3 2 (b) antilog 1/100 -1/2
5) Find log , (a) (1/4 ) -2 = 16 (b) 1/10 = 0.1
USING LOGARITHM TO TRANSFORM DATA :

## Example : 4 10 x = 14 , taking log to the base 10

x = log10 14 = 1.15

log x
Example : 5 = 2.97
10
Therefore, x = 10 2.97 = 933.25

## # Logarithmic transformation of Exponential Functions :

Example : 6 Exponential Functions are generally defined as y = ta x
( in exponential functions , EXPONENT is a VARIABLE )

Example : 7
many biological process are exponenetial , and those can be expressed conveniently as linear function of the
form y = mx + c by using logarithmic transformation :

## y = ta x can be transformed logarithmically as

log y = logt + log ax
10 10 10
= log t + x log a
10 10
Considering a new variable Y defined as log y
10
A log a
and two new constants as = 10 and T = log
10
t

## the above equation becomes : Y = T + Ax or Y = Ax + T

which describes a Linear Function o fthe type y = mx + c

## if Y ( i. e. log 10 y ) is plotted against x

then the GRADIENT of the LINE would be A ( i.e. log 10 a )
and INTERCEPT would be T ( i.e. log 10 t )

( vide chapter 2 )

## The Function y = ax n is an example of Power Function where

EXPONENT is a CONSTANT
Considering a new variable Y = log 10 y , X = log 10 x and constant
A = log 10 a
equation y = ax n can be transformed as
log y log a n log x
10 = 10 + 10 i.e. Y = nX + A giving a Linear Function
where X can be plotted agaist Y with GRADIEN n and INTERCEPT A

## THE EXPONENTIAL CONSTANT :

Logarithm to the base 10 and base 2 are useful as our number system
itself is decimal ( i.e. based on units of 10 ) and the simple biological situation
of the division of a mother cell into two daughter cells.

The third base for logarithm was first introduce by John Napier ( 1550-1617) . It is the number
represented by the e. to assert a value for e following discussion explains the guiding
principle :

## Consider a bacterial culture containing a large number, n0 , of cells with an

unlimited food-supply.

Let it be assumed that in any unit interval of time a certain small fraction ( or,
propor -tion) , r , of the cells divide and that this fraction ( i.e r ) remains
constant for all such unit intervals .

## r n0 of them , will divide to yeild two

In the succeeding interval of time , some of these n0, ( in fact
daugheter cells each. The remaining ( n 0 – rn 0 ) does not divide .

## The number of cells at th end of first interval of time ill become :

n1 = rn0 x 2 + ( n0 – rn0 ) x 1
= 2 rn0 + n0 – rn0
or , n1 = n0 ( 1 + r ) : this population size at time t1.

In the next interval of time rn1 of these cells will divide and ( n1 – rn1 ) will remain
undivided , so that

n2 = rn1 x 2 + ( n1 – rn1 ) x 1
= n1 ( 1 + r )

## Repeating this argument, after t intervals

n t = n t-1 ( 1 + r )
Now,
n1 = n0 ( 1 + r )
n2 = n1 ( 1 + r ) = n0 ( 1 + r ) x ( 1 + r ) = n0 ( 1 + r ) 2
n3 = n2 ( 1 + r ) = n0 ( 1 + r ) 2 x ( 1 + r ) = n0 ( 1 + r ) 3
Generalizing in this way we get ,
nt=n0(1+r)t
If , r=1
n t = n0 2 t
Now let us consider  = 3600 )
and considering that the fraction of cells dividing at each time interval is r ,
we get that at each sub-unit of time interval ( i. e.  ) fraction of cells dividing will be
r /  ( say =  ).
In terms of the new time interval ,considering population size n t-1 we get ,
n t = n t-1 ( 1 +  ) 
Substituting this in equation n t = n0 ( 1 + r ) t , we get ,
nt = n0( 1+ )t (  t = 3600 , when t = 1 )
Replacing  in this expression by r/ the equation becomes ,
nt= n0(1+) rt/
if  is large , that is new time interval is small ,  will be small and close to zero.

## Since  is a fraction , it can be represented as  = 1 /  ; so the equation becomes

nt=n0[(1+1/ )]rt
OR, nt=n0[(1+1/ ) ]rt
Let us consider ,  = (1+1/) , then we have
nt=n0

Following table presents values of  for increasing values of  to six decimal places

  = (1+1/)

1 2.0

10 2 . 593742

100 2 . 704814

1000 2 . 716924

10000 2 . 718146

100000 2 . 718268

1000000 2 . 718280

 e = 2 . 718282

## As  gets larger the CHANGE in  becomes increasingly smaller .

As    ,  approaches a limit ( note the difference in the values of  in the last
two rows in the Table : )
The numerical value of the limit is e = 2 . 718282…. Which is known as
EXPONENTIAL CONSTANT .

Starting with a single parent , general expression for the growth in cell numbers after t generations
is given by the Exponential Function
t
Nt= 2
t
Nt=h2

This is generalized as
x
y = 2
where the Exponential Function x may take all real values .
This equation is further generalized as
x
y = kb

Now ,
x x
Log y = log ( k b ) OR log y = log k + log b OR log y = log k + x log b
Putting y = Y , log k =  and log b = 
We get,
Y=+x
This is an equation for straight line. It is concluded, therefore, that there exists a linear relation
between Y and x .

t
Considering the equation Nt=2 , we get ( deriving as above )
t
log N t = log 2 = t log 2

## Taking the base of the logarithm as 2

log 2 N t = t
[ NOTE :
1) This becomes a linear equation with Y = log 2 N t , x = t and  = 1
2) With  = 0 (  not necessarily equal to unity ) Y is described as proportional to x
3) In mathematical terms the constants  and  are termed , respectively , as
INTERCEPT and SLOPE ( or gradient )